The Warsaw Sisters : [large type] a novel of WWII Poland - Barratt, Amanda, 1996- (Thorndike Press large print Christian fiction series., 2024)
"On a golden August morning in 1939, sisters Antonina and Helena Dąbrowska send their father off to defend Poland against the looming threat of German invasion. The next day, the first bombs fall on Warsaw, decimating their beloved city and shattering the world of their youth. When Antonina's beloved Marek is forced behind ghetto walls along with the rest of Warsaw's Jewish population, Antonina turns her worry into action and becomes a key figure in a daring network of women risking their lives to shelter Jewish children. Helena finds herself drawn into the ranks of Poland's secret army, joining the fight to free her homeland from occupation. But the secrets both are forced to keep threaten to tear the sisters apart--and the cost of resistance proves greater than either ever imagined. Shining a light on the oft-forgotten history of Poland during WWII and inspired by true stories of ordinary individuals who fought to preserve freedom and humanity in the darkest of times, The Warsaw Sisters is a richly rendered portrait of courage, sacrifice, and the resilience of our deepest ties"--